Evolution of the ionospheric mapping and modelling during the last four decades. - Cander, L.R.; Zolesi, B. (Física de la Tierra, 2000)
Since- tite- be-ginning of tite- ionaspite-ric discavery, ianosphe-ric mapping ano] madelling itas be-en tite- subject of an intense- ano] cantinuous work by geapitysicists and radiouse-rs witit tite- aim to understand bette-r aur environment ano] to improve o]ive-rsity ab applicatians in radia-propagatian. `me evalutian in the last faur decades of tite-se studies, brom HP system design, circuit planning and perfonnance- predictions ta real-time control of tite ianosphe-ric paraine-te-rs lar space- we-athe-r purposes ano] Earth satellite reporteo] itere by a sitart revie-w of tite- principal ano] accepted communications, itas be-en metbods. Changes of tite needed appflcations, fram global ta regional madelling ano] from long ta shart-term or e-ven instantane-aus ano] now-casting mapping, connected with rapid progre-ss of tite competer sysLems bave- be-en e-ansio]e-re-d tao.